Tinjauan Yuridis Terhadap Tindak Pidana Pemerkosaan yang Menyebabkan Kematian (Studi) Kasus Pengadilan Negeri Kendal - Pande Komang Satya Parama Hamsa; I Nyoman Gede Sugiartha; Ni Made Sukaryati Karma (Warmadewa Press, 2021)
Rape is a serious crime because it harms the victim, disturbs the future, and causes a very bad influence on the victim, even death. The purpose of this study is to reveal the criminal sanctions against the crime of rape that causes death and the judge's considerations in deciding the crime of rape that causes death. The method used in this research is normative research with a case and legislation approach. Sources of legal materials used in the form of secondary and primary legal sources which are then analyzed descriptively. The results of the study revealed that the perpetrator violated the provisions of Article 285 , 288 paragraph (3), 359, 291 paragraph (2) of the Criminal Code, Article 76D and 81 paragraph (1) of Law Number 35 of 2014 on amendments to the Law. Number 23 of 2002 concerning Child Protection, and violates the provisions of Article 71 of Law no. 11 of 2012 concerning the Juvenile Criminal Justice System. The judge sentenced the defendant to 4 years in prison.